2005
DOI: 10.1002/imhj.20061
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the social behavior of infants: Use of the ADBB Scale and relationship to mother's mood

Abstract: Infants can show a range of social behavior when interacting with their main caregiver. Previous work has demonstrated that when the caregiver is depressed, the infant may demonstrate withdrawn behavior not only to this person but also to others. This pilot study used a relatively new assessment tool, the Alarme Distress de Bebe Scale (ADBB; Guedeney and Fermanian, 2001), to assess the social behavior of 44 infants during a routine physical checkup. Results indicated that withdrawn infant social behavior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
2
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 19 publications
9
48
2
5
Order By: Relevance
“…Infants of mothers who report to be more depressed or anxious since childbirth have significantly higher ADBB scores [22,23]. These studies confirmed the correlation between maternal psychologi- cal pathology and infant withdrawal behavior.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Infants of mothers who report to be more depressed or anxious since childbirth have significantly higher ADBB scores [22,23]. These studies confirmed the correlation between maternal psychologi- cal pathology and infant withdrawal behavior.…”
Section: Discussionsupporting
confidence: 64%
“…An important point about trans-cultural validity is that five studies found the same cut-off score of 5. The scale has been shown to have good reliability and validity [3,22].…”
Section: Open Accessmentioning
confidence: 99%
“…A maior parte das pesquisas desenvolvidas com populações de baixo risco em situação de consulta de rotina pediátrica/puericultura encontrou taxas entre 6,9% e 14% (Puura et al, 2010;Mäntymaa et al, 2008;Lopes et al, 2008;Guedeney et al, 2008;Guedeney et al, 2012), embora outros estudos tenham encontrado taxas entre 25% e 34,1% para população semelhante (Plevak et al, 2012;Mathey et al, 2005). Entre os bebês sob condição de risco avaliados nesta mesma situação -prematuros ou filhos de mães usuárias de álcool durante a gestação -, as taxas encontradas situam-se entre 3,5% e 27,1% (Braarud et al, 2013;Molteno, 2014).…”
Section: Desenvolvimento Psíquico Dos Bebês: Uma Perspectiva Bidireciunclassified
“…Outro estudo confirma a ausência de associação entre retraimento e estado depressivo materno atual, mas estabelece associação com queixa materna de depressão, ansiedade, tristeza ou irritabilidade desde o nascimento, indicando a necessidade de avaliação mais aprofundada e retrospectiva do estado de saúde mental materno e não apenas de seu estado atual (Mathey et al, 2005 …”
Section: Desenvolvimento Psíquico Dos Bebês: Uma Perspectiva Bidireciunclassified
See 1 more Smart Citation